Quality control system for secondary battery and quality control method using the same

The quality management system addresses the challenge of detecting defects in secondary battery electrode mixture sheets by correlating manufacturing and structural information with performance data, enhancing yield and operational reliability.

JP2025065622APending Publication Date: 2025-04-22HITACHI HIGH TECH CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023174939
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Current methods for quality control in secondary battery manufacturing fail to detect mixing defects and uneven distribution of constituent materials in electrode mixture sheets, leading to performance defects and reduced yield during both manufacturing and operation.

Method used

A quality management system that stores manufacturing, structure, and performance information, allowing for efficient acquisition and feedback of characteristic amounts affecting battery performance, thereby improving yield and reducing operational risks.

Benefits of technology

This system enables the detection of performance defects in real-time, improving manufacturing efficiency, reducing waste, and ensuring higher quality battery production by correlating structural information with performance data.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065622000001_ABST
    Figure 2025065622000001_ABST
Patent Text Reader

Abstract

To improve the manufacturing yield of secondary batteries or reduce the risk of abnormalities during operation.SOLUTION: A quality control system for secondary batteries includes a storage unit which associates and stores: manufacturing information related to the manufacture of an electrode mixture sheet applied to a positive electrode and / or a negative electrode of a secondary battery; structure information including at least one of presence or absence of defects and cracks within the electrodes, a ratio of constituent materials within the surface or in a thickness direction of the electrode mixture sheet, the size of an aggregate comprising constituent materials, cracks occurring inside an electrode active material particle, and a ratio of voids where constitutional materials are not present; and performance information including at least one of capacity at initial charge / discharge, a charge / discharge efficiency that is a capacity ratio at charge / discharge, battery capacity when charge or discharge current is changed, and AC resistance and DC resistance at a predetermined charging rate.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a quality control system for secondary batteries and a quality control method using the same. [Background technology]

[0002] In order to reduce CO2 emissions, there is an increasing need to use fossil fuel-free secondary batteries as the driving force for mobile devices. In addition, in the power grid, it is necessary to increase the proportion of renewable energy such as solar power generation and wind power generation instead of fossil fuels as an energy source to cover electricity, and there is an increasing need for electric energy storage systems using secondary batteries as an adjustment power to suppress output fluctuations. Against this background, there is an increasing need for the manufacture of secondary batteries, typified by lithium-ion secondary batteries.

[0003] Issues with secondary batteries include improving the energy efficiency and resource efficiency involved in their manufacture. To achieve this, it is necessary to increase the yield of the batteries produced, but this is difficult to achieve due to material variations within the battery and poor quality of battery internal components caused by conditions that are difficult to control. Among battery internal components, electrode composite sheets are one that have a strong impact on yield.

[0004] This is a secondary battery that contains an active material that stores electric charge, a conductive assistant that conducts electrons to the active material, and a binder that binds them together, and it is believed that the presence or absence of defects during manufacturing, the aggregate size, and the dispersion state of the constituent materials affect the battery performance. As publicly known techniques for improving yield, various methods for inspecting electrode composite sheets after manufacture have been disclosed.

[0005] Patent Document 1 discloses a method for determining the presence or absence of defects and the type of defects in a roll-shaped electrode mixture sheet having an active material layer formed on at least one surface of a current collector, by photographing an electrode mixture sheet after pressing with an infrared camera, processing the obtained infrared image to increase the resolution of the image, and detecting defective areas by comparing the image after the high-resolution processing with a previously obtained image of the defect.

[0006] Patent Document 2 discloses a method for detecting folds, wrinkles, etc., by including a process of applying markings to predetermined positions on an electrode mixture sheet before winding, and a process of detecting the amount of positional deviation between markings applied to adjacent electrode sheets among the markings applied to multiple wound electrode mixture sheets.

[0007] Patent Document 3 discloses a method of irradiating the surface of a thin electrode composite sheet wound into a roll with inspection light, capturing images of the transmitted light, specularly reflected light and scattered light, and analyzing the captured image data in an image processing unit to record the types of defects present in the sheet (black defects, white defects, gloss defects, fiber bundle defects, resin deficiency defects, pinhole defects), as well as the locations and sizes of the defects, on a recording medium. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2016-143641 A [Patent Document 2] JP 2015-133259 A [Patent Document 3] JP 2010-272250 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, in Patent Documents 1 to 3, although it is possible to identify the presence or absence of obvious defects such as electrode defects, it is difficult to grasp poor mixing or uneven distribution of the constituent materials in an electrode composite sheet that does not have such obvious defects, and this has led to the problem that performance defects at the time of manufacture and shipment or during battery operation cannot be detected in advance. In addition to the fact that performance defects at the time of manufacture and shipment cannot be detected in advance, the yield during the manufacturing process is reduced, and batteries are manufactured using defective electrodes, resulting in the loss of time and energy. In addition, the fact that performance defects during battery operation cannot be detected in advance reduces the operating rate of devices and systems that use the corresponding batteries.

[0010] In general, in the battery material and process design stage, if the battery performance after production is not as desired, the electrodes can be observed using an electron microscope or the like to clarify the reason, and the presence or absence of the above-mentioned poor mixing or uneven distribution can be confirmed, and the results can be reflected in the material and process design. However, since these observations take time, they are often performed as offline evaluations by taking out the relevant samples after production and evaluation, and have not been used for inspection in the manufacturing process. In addition, even if electrode structure information can be obtained by sampling inspection of the produced electrode mixture sheet, the method for extracting structural factors that affect battery performance has not been established, and the correlation between battery performance at the time of inspection and deterioration characteristics during operation is unclear, making it difficult to feed back the inspection results to the manufacturing process.

[0011] As described above, in the manufacturing process of secondary batteries based on the currently publicly available information, uneven distribution of electrode materials, structural defects, and insufficient voids that may occur during the manufacturing of electrode composite sheets used as positive electrodes (used as an abbreviation for positive electrodes) or negative electrodes (used as an abbreviation for negative electrodes) are not detected during the process, resulting in poor performance at the time of shipping inspection and reduced manufacturing efficiency. In addition, even if the above information is obtained through electrode inspection, it is difficult to provide feedback to the electrode manufacturing process because the correlation between battery performance and degradation characteristics is unclear, resulting in reduced manufacturing efficiency.

[0012] The object of the present invention is to solve the above-mentioned problems and efficiently obtain features that strongly affect battery performance from electrode composite sheets during the manufacturing process, and to feed these back as control items to the manufacturing conditions, thereby improving product yields or reducing the risk of abnormalities during operation. [Means for solving the problem]

[0013] The present invention has the following configuration for solving the above problems. a quality control system for a secondary battery having a storage device that stores, in association with each other, the manufacturing information, structural information, and performance information; information relating to the manufacturing of an electrode mixture sheet that is applied to the positive and / or negative electrodes of a secondary battery, the manufacturing information including at least one of the material specifications, the manufacturing lot of the material, the mixing conditions, the coating conditions, and the pressing conditions for forming the electrode mixture sheet; information relating to the structure of the electrode mixture sheet measured after manufacturing, the structural information including at least one of defects and cracks in the electrode, the ratio of the constituent materials in the plane and thickness direction of the electrode mixture sheet, the aggregate size made of the constituent materials, cracks that occur inside the electrode active material particles, and the void ratio where no constituent materials are present; and information relating to the performance of a secondary battery manufactured using the electrode mixture sheet, the performance information including at least one of the capacity at the initial charge and discharge, the charge and discharge efficiency which is the ratio of the capacity at the time of charge and discharge, the battery capacity when the charge or discharge current is changed, and the AC resistance and DC resistance at a specified charge rate. Effect of the Invention

[0014] According to the present invention, by efficiently acquiring features that strongly affect battery performance from an electrode mixture sheet during the manufacturing process and feeding these back to the manufacturing conditions as control items, it is possible to improve product yield or reduce the risk of abnormalities during operation.

[0015] Problems, configurations and effects other than those described above will become apparent from the following description of the embodiments. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a diagram showing an example of a configuration in a planar direction of a battery to be inspected according to the present invention; [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of an example of the cross-sectional configuration of a battery to be inspected according to the present invention. [Diagram 3] FIG. 2 is a diagram showing a schematic example of a cross-sectional configuration of an electrode mixture sheet constituting a battery to be inspected according to the present invention. [Figure 4] 1A to 1C are diagrams illustrating an example of a manufacturing process for a battery to be inspected according to the present invention. [Diagram 5] FIG. 2 is a diagram illustrating an example of a process flow according to the inspection system of the present invention. [Figure 6] 1A to 1C are diagrams illustrating a process of extracting a sample to be inspected from an electrode mixture sheet during production in the inspection process of the present invention. [Figure 7] FIG. 2 is a diagram illustrating an example of a process flow according to the inspection system of the present invention. [Figure 8] FIG. 2 is a diagram showing an example of a process flow for constructing a performance and deterioration prediction model in the inspection system of the present invention. [Figure 9] FIG. 2 is a diagram showing a schematic diagram of the relationship between battery internal state parameters and the voltage-capacity curve and resistance-capacity curve of a battery for use in constructing a performance and deterioration prediction model related to the inspection system of the present invention. [Figure 10] FIG. 2 is a diagram showing an example of a process flow for constructing a performance and deterioration prediction model in the inspection system of the present invention. [Figure 11] FIG. 2 is a diagram showing a scanning electron microscope image of a surface and the results of composition analysis by energy dispersive X-ray spectroscopy as an example of structural information relating to an embodiment of the present invention. [Figure 12] FIG. 2 is a diagram showing a scanning electron microscope image of a cross section of an electrode and composition distribution results obtained by energy dispersive X-ray spectroscopy, as an example of structural information relating to an embodiment of the present invention. [Figure 13] FIG. 13 is a diagram showing an image analysis flow for evaluating the distribution of constituent materials from a scanning electron microscope image of a surface as an example of structural information according to an embodiment of the present invention. [Figure 14] FIG. 13 is a diagram showing an example of the results of evaluating the distribution of constituent materials from a scanning electron microscope image of a surface, as an example of structural information according to an embodiment of the present invention. [Figure 15] FIG. 4 is a diagram showing a discharge rate characteristic as an example of battery performance information according to an embodiment of the present invention. [Figure 16] FIG. 13 is a diagram showing the results of AC impedance measurement for evaluating ion conduction resistance in an electrode as an example of battery performance information according to an embodiment of the present invention. [Figure 17] FIG. 4 is a diagram showing a discharge capacity maintenance rate during a charge / discharge cycle as an example of battery performance information according to an embodiment of the present invention. [Figure 18] FIG. 1 shows a correlation between the area ratio of intermediate color regions in a backscattered electron image, which is one piece of structural information relating to an embodiment of the present invention, and battery performance ((a) ionic conduction resistance in an electrode, (b) the ratio of 5C discharge capacity to 0.2C discharge capacity in the discharge rate characteristics, (c) the discharge capacity retention rate in a charge-discharge cycle test, and (d) the rate of change in the utilization rate (mp) of the positive electrode active material during charge-discharge cycles). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, modes for carrying out the present invention (hereinafter referred to as "embodiments") will be described with reference to the drawings as appropriate.

[0018] In describing the inspection system for the battery manufacturing process of the present invention, first, <structure and constituent materials of the lithium ion battery> and <manufacturing process of the lithium ion battery> will be described, and then, the inspection system for the secondary battery manufacturing process, which is an embodiment of the present invention, will be described. Note that the secondary battery to which the present invention is applied is not limited to the lithium ion battery, and is merely shown as an example.

[0019] <Structure and constituent materials of lithium-ion batteries> The structure of one embodiment of a lithium ion battery will be described with reference to Figures 1 and 2. Figure 1 is a conceptual diagram showing an example of a cross section of a lithium ion battery.

[0020] In Fig. 1, a cell (battery cell, secondary battery) 100 includes an electrode occupancy portion 1, a positive electrode terminal (tab) 2, a negative electrode terminal (tab) 3, an electrolyte 4, a separator 5, and an exterior material 6. The exterior material 6 is made of a laminate film or a similar material. In Fig. 1, a plurality of separators and electrodes are laminated and sealed with a laminate film, but the laminate may also be wound and enclosed in a cylindrical exterior material or a rectangular exterior material.

[0021] Fig. 2 is a conceptual diagram showing an example of a cross section of the electricity storage element (constituent element of the electricity storage mechanism) of the cell in Fig. 1. In Fig. 2, the electricity storage element of the cell includes a positive electrode 11, a negative electrode 12, and a separator 5. Note that an electrolyte 4 as a battery is impregnated into micropores of the positive electrode 11, the negative electrode 12, the separator 5, etc. Therefore, the electrolyte 4 is not shown in Fig. 2.

[0022] In addition, in Fig. 2, the electricity storage element has positive electrodes 11 and negative electrodes 12 arranged alternately with separators 5 sandwiched therebetween. For example, polypropylene is used as the separator 5. However, other than polypropylene, microporous films and nonwoven fabrics made of polyolefins such as polyethylene can also be used as the separator 5. Note that Figs. 1 and 2 are conceptual diagrams showing an example of a cross section of a lithium ion battery and an example of a cross section of an electricity storage element of a cell, and the positional relationship and size of each component are not limited to those shown in the drawings.

[0023] The positive electrode 11 and the negative electrode 12 are each formed by forming a sheet of a mixture of an appropriate electrode active material, a conductive agent, a binder, etc., on a current collector foil of an appropriate metal. In the present invention, these are referred to as "electrode mixture sheets."

[0024] In the case of a lithium-ion battery cell, which is one of the objects to be inspected by the present invention, any current collector can be used without being limited by material, shape, manufacturing method, etc.

[0025] <Positive electrode 11> The current collecting foil of the positive electrode 11 may be any of aluminum foil having a thickness of 10 to 100 μm, aluminum perforated foil having a thickness of 10 to 100 μm and a pore size of 0.1 to 10 mm, expanded metal, and foamed metal plate. In addition to aluminum, stainless steel, titanium, and the like may also be used as the material.

[0026] The electrode active material of the positive electrode 11 preferably contains a reactive species therein. The reactive species of a lithium ion battery is lithium ions. In this case, the electrode active material contains a lithium-containing compound capable of reversibly inserting and detaching lithium ions. The types of electrode active material of the positive electrode 11 include, for example, lithium cobalt oxide, lithium manganese-substituted cobalt oxide, lithium manganate, lithium nickel oxide, lithium transition metal phosphate such as olivine-type lithium iron phosphate, Li w Ni x Co y Mn z O2 (where w, x, y, and z are 0 or positive values).

[0027] <Negative electrode 12> The current collector foil of the negative electrode 12 may be a copper foil having a thickness of 10 to 100 μm, a perforated copper foil having a thickness of 10 to 100 μm and a pore size of 0.1 to 10 mm, an expanded metal, a foam metal plate, or the like. In addition to copper, stainless steel, titanium, or the like may also be used as the material. The electrode active material of the negative electrode 12 contains a material capable of reversibly inserting and detaching lithium ions. The types of electrode active material of the negative electrode 12 include, for example, natural graphite, a composite carbonaceous material in which a coating is formed on natural graphite by a dry CVD method or a wet spray method, artificial graphite produced by firing a resin material such as epoxy or phenol, or a pitch-based material obtained from petroleum or coal, silicon (Si), graphite mixed with silicon, a non-graphitizable carbon material, lithium titanate Li4Ti5O 12 etc. can be used.

[0028] In addition, multiple materials can be selected and applied as the active materials for the positive and negative electrodes as necessary. Figure 3 is a conceptual diagram showing the cross section of an electrode in a lithium-ion battery, where (a) is an electrode made of a single active material A 312, and (b) is a composite electrode made of two active materials A 312 and B 315.

[0029] <Electrolyte> The electricity storage element (constituent elements of the electricity storage mechanism) includes a positive electrode 11, a negative electrode 12, a separator 5, and an electrolyte 4. In the case of a lithium-ion battery, the electrolyte may be, for example, an aprotic organic solvent such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate (MPC), or ethyl propyl carbonate (EPC). Alternatively, the electrolyte may be prepared by dissolving lithium salts such as lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium iodide, lithium chloride, lithium bromide, LiB(OCOCF3)4, LiB(OCOCF2CF3)4, LiPF4(CF3)2, LiN(SO2CF3)2, and LiN(SO2CF2CF3)2 in a solvent of the above-mentioned two or more kinds of mixed organic compounds. Alternatively, the electrolyte may be prepared by dissolving a mixed lithium salt of the above-mentioned two or more kinds.

[0030] The constituent solvent of the above-mentioned electrolyte solution is generally highly volatile, and the electrolyte solution often has a volatilization temperature of less than 25°C. In addition, in one embodiment of the present invention, a lithium ion conductive liquid having a volatilization temperature of, for example, 100°C or higher can be used. Specifically, ionic liquids and solvated ionic liquids can be mentioned. Furthermore, a solid electrolyte can be used instead of the electrolyte solution.

[0031] <Lithium-ion battery manufacturing process> Figure 4 shows a schematic diagram of an example of the manufacturing process for lithium-ion batteries. After mixing the constituent materials, the electrode active material, conductive additive, and binder, they are formed into an electrode composite sheet. In this case, it is common to disperse each material in a solvent to make a slurry, which is then applied to a current collector foil using a blade coater or die coater and dried to form a sheet. However, it is also possible to mix the solid active material, conductive additive, and binder without dispersing them in a solvent by applying pressure with a roll or the like, and then disperse and pressurize them in this state on the current collector foil to form a sheet.

[0032] In addition, it is also possible to manufacture an electrode composite sheet for a solid-state battery in which the electrolyte is replaced with a solid electrolyte by adding and mixing the above-mentioned materials. The electrode composite sheet formed on the current collector foil is generally cut to a predetermined size, laminated with a separator and a solid electrolyte, and stored in a battery exterior, and then injected and sealed to form a battery cell. In addition, by charging and discharging the manufactured battery under appropriate conditions to form a stable film between the electrode composite sheet and the electrolyte, the performance of the battery can be maintained at a high level during subsequent operation. This is called conditioning or aging treatment.

[0033] After that, performance tests are conducted before shipment, and batteries that show the required performance are shipped as normal products. Performance test items include, for example, the capacity at the first charge / discharge and the charge / discharge efficiency, which is the ratio of the capacity to the charge / discharge efficiency, the battery capacity when the charge / discharge current is changed (rate characteristics), and the AC resistance and DC resistance at a specified charging rate (SOC: State Of Charge).

[0034] If any of the inspection items fail to meet the guaranteed performance, the cell is deemed defective and either discarded without being shipped or disassembled and materials recovered as necessary. This process also consumes energy, so in manufacturing processes with a high defect rate, the amount of energy consumed and the cost per battery cell produced decreases, which is an issue. If this defect determination cannot be made until the final process on the production line, the energy used to manufacture the defective product will also be wasted, further reducing efficiency.

[0035] <Inspection methods in the manufacturing process> As one method for solving the problem of the deterioration in manufacturing efficiency described above, the present invention presents a method in which, after the electrode mixture sheet is manufactured, a sample piece is extracted from a part of it, and during a process of inspecting its structure, structural information is quantified as a feature and used as a control item for determining the quality of the electrode mixture sheet.

[0036] An inspection method according to one embodiment of the present invention is shown in a flowchart in Figure 5. In this flowchart, three types of information, namely, manufacturing information, structure information, and performance information, are acquired and stored in an inspection system (quality control system).

[0037] The manufacturing information includes material specifications for forming the electrode mixture sheet, the production lot of the material, mixing conditions, coating conditions (atmosphere, slurry viscosity, coating speed, drying temperature), pressing conditions (pressure, pressing time), and the like.

[0038] Examples of structural information include the presence or absence of defects or cracks in the electrode, as well as the ratio of constituent materials (active material, conductive assistant, binder) in the surface and thickness direction of the electrode composite sheet, the aggregate size of the constituent materials, cracks occurring inside the electrode active material particles, and the void ratio where no constituent materials exist. In addition, three-dimensional information of these items, that is, the distribution of the above-mentioned items in the sheet thickness direction, can also be used as structural information. Examples of inspection methods for obtaining the above-mentioned structural information include a scanning electron microscope (SEM), an optical microscope, and a blackness measurement method. In addition, element distribution information in a sample obtained by energy dispersive X-ray spectroscopy (EDX) attached to a scanning electron microscope can also be applied as structural information.

[0039] In addition, since the inspection is performed during the manufacturing process, it is necessary to easily sample a sample piece, and one embodiment of the present invention can include a method in which a part of a wound body made of an electrode composite sheet after manufacturing is extracted by a punching process and fixed to a holder for the above-mentioned inspection device, as shown in Fig. 6. Other methods for extracting a sample include, but are not limited to, a method of taking it out by processing using a laser.

[0040] By taking a SEM secondary electron image of the surface of the electrode composite sheet fixed to the inspection holder and observing the surface morphology, defects in the electrode can be detected, and the degree of defects can be quantified by the number of defects per unit area and the area ratio. Similarly, cracks in the active material particles can also be detected by the secondary electron image, and the degree of defects can be quantified by the number of cracks in the active material per unit area or the total crack length.

[0041] In addition, by using a backscattered electron image of an SEM, an observation image having a contrast reflecting the atomic weight of the constituent elements can be obtained, and by quantifying the size and area ratio of the regions with different contrast, the aggregate size, the ratio of the constituent materials (active material, conductive additive, binder), and the void ratio can be quantified. In addition, to obtain information in the thickness direction of the electrode mixture sheet, cross-sectional observation after punching can be used, and the electrode mixture sheet extracted from the roll can be peeled off from the current collector foil, and surface information of the peeled surface close to the current collector foil can be obtained by the above-mentioned method.

[0042] Performance information is obtained during aging and shipping inspection of manufactured cells, and includes the capacity at the time of the initial charge and discharge mentioned above, the charge and discharge efficiency which is the ratio of the capacity to the charge and discharge efficiency, the battery capacity when the charge or discharge current is changed (rate characteristics), and the AC resistance and DC resistance at a specified charging rate (SOC: State Of Charge).

[0043] In the inspection system of the present invention, the correlation between the acquired structural information and performance information is formulated, and this is used as a performance prediction model. The structural information of a newly manufactured electrode mixture sheet is used as an input for the performance prediction model, and the battery performance when the corresponding electrode mixture sheet is applied is predicted in advance. At this time, if the predicted performance does not meet the guaranteed performance, the corresponding electrode mixture sheet can be omitted from the manufacturing process to prevent battery defects in the later stages. Specifically, it is determined whether there are cracks or peeling in the electrode as structural information, and then it is determined whether the performance output from the performance prediction model meets the guaranteed performance, and only the electrode mixture sheets that pass both judgments are cut and stacked to proceed with the battery production.

[0044] On the other hand, for electrodes that do not meet the criteria, they are removed from the process, and it is determined that the manufacturing conditions used to form the electrode composite sheet were not appropriate, and the manufacturing conditions can be updated. By repeatedly carrying out the above inspections and updating the manufacturing conditions, it is possible to reduce the risk of defects in the manufacturing process and increase manufacturing efficiency.

[0045] FIG. 7 shows a flowchart of an inspection system (quality control system) according to one embodiment of the present invention. Here, in addition to the manufacturing information and structure information shown in FIG. 5, operation information, deterioration information, and abnormality information can be used as information used for inspection. The operation information here indicates the usage history of a battery cell incorporated into a storage battery system after shipment, and can mainly be time-series data such as battery voltage, current, and temperature detected by a battery management system (BMS) of the storage battery system. Moreover, deterioration information refers to changes in battery performance due to the above-mentioned operation. This deterioration information can also be estimated by analyzing BMS data.

[0046] When a storage battery system is used under operating conditions suited to the battery specifications, performance will deteriorate, but because performance progresses according to a previously predicted trend, the system can be used in a planned manner. However, if a sudden deterioration occurs that differs from the predicted trend, it is determined that a malfunction has occurred in the system, and operation may be halted. In this case, it is necessary to identify the reason for the abnormality and take corrective measures according to the reason. By comparing the deterioration information obtained by inputting the structural information in Figure 7 with the abnormality information, it is possible to determine whether the cause of the abnormality occurred during the manufacture of the battery and electrode composite sheet, or whether the operating conditions were inappropriate.

[0047] <Formulation method for correlation between structural information, performance information, and deterioration information> In Figures 5 and 7, by formulating the correlation between structural information and performance information or degradation information, it is possible to reduce the manufacturing defect rate of batteries and clarify the causes of system malfunctions. Three examples of this formulation method are described below. For this formulation, it is necessary to prepare multiple electrode composite sheets and obtain structural information and performance / degradation information for each when considering materials and processes to determine the specifications of the battery to be manufactured, or when designing and trial-running a production line. Below, we will show a method for formulating the correlation using the obtained information, but the method is not limited to this.

[0048] (i) In the design stage of the materials and process of the target battery, or during the trial operation of the production line, the manufacturing conditions are intentionally controlled to produce electrode composite sheets with different structures. For a group of electrodes in which only specific manufacturing conditions have been changed, structural information is obtained from electrode inspections, and performance information is obtained from pre-shipment inspections of the manufactured batteries. Here, feature quantities indicating structural and performance information (hereinafter referred to as structural parameters and performance parameters) are extracted, and the relationship between the performance parameters or degradation parameters and the structural parameters are used as objective variables is formulated by regression analysis, and the formula is stored in a storage device.

[0049] In Fig. 5 to Fig. 7, the structural information of the electrode composite sheet extracted from the manufacturing process is input into the corresponding formula to predict performance. Fig. 8 shows an example of a flow for constructing a performance / deterioration prediction model using the above method. The manufacturing conditions for the electrode composite sheet for acquiring information are determined, electrodes and batteries are produced based on the conditions, and the corresponding structural parameters and performance / deterioration parameters are acquired multiple times, and a prediction model is constructed by regression analysis. This is repeated until the correlation coefficient falls below a predetermined value, and a performance prediction model is obtained. There are no particular regulations regarding the correlation formula obtained by regression analysis, and it can be a polynomial function, exponential function, logarithmic function, power function, etc., and any function that clearly shows the correlation can be selected as appropriate.

[0050] (ii) In addition, similar to (i), the manufacturing conditions are intentionally controlled during the design stage of the material and process of the target battery or during the trial operation of the manufacturing line to produce electrodes with different structures. In this case, multiple manufacturing conditions are changed, multiple groups of electrode composite sheets with different structural parameters are prepared, and the performance parameters of the batteries to which each electrode is applied are evaluated. By performing multiple regression analysis on the obtained parameter group, the performance parameters are expressed as multidimensional functions of the structural parameters, and this is stored in a memory device. This process is the same as in Figure 8. However, the amount of information required for formulation increases as the number of types of structural parameters handled increases. It is also possible to use machine learning to formulate with a small amount of information.

[0051] (iii) In addition, in the formulation, a method utilizing a battery model that reflects the phenomenon that progresses inside the battery can also be used. Specifically, the charge / discharge curve of the battery can be reproduced using battery internal state parameters that are related to the structural information, and performance information and degradation information can be predicted. Regarding the battery internal state parameters, a known technique, for example, a method described in Kohei Honkura, Ko Takahashi, and Tatsuo Horiba, Journal of Power Sources Vol.196 Issue 23 (2011), Pages 10141-10147., in which the "battery internal state parameters" are estimated as feature quantities derived from the materials inside the battery from changes in the shape of a voltage-capacity curve or a resistance-capacity curve obtained during charging or discharging of the manufactured battery, can be used.

[0052] An example of the reactions occurring inside a battery and the corresponding internal state parameters of the battery is shown in Figure 9. The capacity dependence of the potential and resistance of the manufactured electrodes (positive electrode, negative electrode) is specific to the type of active material used in the electrodes, provided there are no fatal structural abnormalities, and the voltage-capacity curve of the battery can be expressed as the difference between the potential-capacity curves of the positive electrode and negative electrode, and the resistance-capacity curve of the battery can be expressed as the sum (ohmic resistance) of the resistance-capacity curve of each electrode and the electronic resistance and ionic resistance of the components.

[0053] When structural abnormalities occur in the electrodes or material deterioration progresses due to operation, the length of the positive and negative electrodes in the capacity axis or resistance axis direction changes, and the relative positions of the positive and negative electrodes in the capacity axis direction change, resulting in a change in battery performance. In the above-mentioned document, the "battery internal state parameter," which is an index of the material state inside the battery, can be quantitatively evaluated from the change in the shape of the voltage-capacity curve and resistance-capacity curve of the battery immediately after manufacture or during operation.

[0054] Figure 9(a) shows the internal state parameters of the battery, i.e., the utilization rate of the active material in the positive electrode (m p ), the utilization rate of the active material in the negative electrode (m n ), and ion loss due to electrolyte decomposition on the positive and negative electrode surfaces (δ p , δn ), the ohmic resistance in the battery (R0, the electronic resistance + ionic resistance of the components), the rate of increase in ion diffusion resistance in the positive and negative electrodes (a p , a n ) is shown. As shown in Fig. 9(b)(c), m p and m n affects the expansion / contraction of the positive and negative curves in the voltage-capacity and resistance-capacity curves in the horizontal direction. p and δ n is the parallel shift (shift) of each curve in the capacity axis direction. Ro corresponds to the baseline of the battery resistance value in the resistance-capacity curve, and a p , a n is the magnification on the vertical axis (resistance axis) of the resistance-capacity curves of the positive and negative electrodes.

[0055] The structural information obtained by SEM or optical microscope is closely related to these battery internal state parameters. For example, the ratio of the constituent materials (active material, conductive additive, binder) in the electrode composite sheet surface is m p , m n , and R o For example, in an electrode where the binder material is unevenly distributed on the surface, the electronic and ionic resistance on the surface tends to increase, resulting in R o In addition, the aggregate size increases with R0, a p , a n The cracks that occur inside the electrode active material particles are p , a n , porosity is thought to affect R0.

[0056] In addition, as the battery continues to operate and the material degradation progresses, the material parameters change in the direction of degradation (m p , m n :decrease, δ p , δ n , a p , a n , R oThe rate of change in the utilization rate m p and resistance increase rate a p , the ohmic resistance R0 is easily changed, and these operating quantities, for example, the change in operating time, i.e., dm p / dt, da p / dt, dR o The absolute value of / dt tends to increase. The same is true for the negative electrode.

[0057] Figure 10 is a schematic diagram showing the flow of preliminary tests and regression analysis for constructing a performance / deterioration prediction model by using the battery internal information parameters. In order to obtain the correlation between the "structural information" and "performance information" required in Figure 5 using the above battery internal state parameters, it is first necessary to prepare an electrode composite sheet constructed under various manufacturing conditions in a preliminary test before the production line is operated. Next, the "structural parameters" extracted as numerical values ​​from the image information showing the structure of this electrode composite sheet and the "battery internal state parameters" extracted from the battery using that electrode are obtained. Then, by obtaining the correlation between the two by regression analysis, it is possible to predict the internal state parameters of a battery using an electrode having any structural parameters. Next, the predicted internal state parameters can be used to reproduce the voltage-capacity curve and resistance-capacity curve of the battery as shown in Figures 9(b) and (c), and the initial performance information (capacity, resistance, input / output characteristics) can be predicted.

[0058] To derive the correlation between "structural information" and "deterioration information" required in Figure 7, the rate of change of each battery internal parameter versus the battery operation amount (operating time, total amount of electricity charged and discharged, number of charge and discharge cycles) is obtained in a preliminary test, and the relationship between this rate of change and the "structural parameters" is formulated by regression analysis. Next, the structural parameters extracted from the electrode composite sheet at the time of manufacture are input and integrated against the operation amount, making it possible to predict the battery internal parameters after a certain period of time, and by reproducing the discharge curve using the battery internal state parameters, it is possible to predict the battery performance after a certain period of time.

[0059] In the following, we will introduce an example to more specifically illustrate the inspection system (quality control system) in the manufacturing process of secondary batteries according to the present invention. The performance prediction model and degradation prediction model used in the inspection system of the present invention are constructed by controlling a large number of manufacturing conditions and using the structure information and performance information at that time, but here we will use a simplified example to clearly explain the concept of the inspection system. EXAMPLES

[0060] <Inspection system focusing on the binder distribution state in positive electrode composite sheets> The test subject was a positive electrode composite sheet with NCM (Li(Ni,Co,Mn)O2) as the active material, and the drying conditions were changed as manufacturing conditions to examine the correlation between the structure information and performance information. Table 1 shows examples of positive electrode composite sheets (positive electrodes A to D) that were applied to the construction of the performance prediction model and the degradation prediction model.

[0061] [Table 1]

[0062] NCM powder, which is the active material, acetylene black, which is the conductive additive, and PVdF, which is the binder, were mixed in a weight ratio of 90:6.5:3.5, respectively, and N-methyl-2-pyrrolidone was added as a solvent to prepare a slurry. The prepared slurry was applied to an Al foil with a thickness of 15 μm using a comma coater, and dried in a drying oven for approximately 10 minutes. The coating amount was 24 mg / cm2 (one side) in terms of weight after drying. The drying temperature was changed between 100°C and 160°C, as shown in Table 1.

[0063] Figure 11 shows the results of observing the morphology of two types of positive electrode composite sheets, positive electrode B (dried at 120°C) and positive electrode D (dried at 160°C), from the coated surface using a scanning electron microscope (SEM) and evaluating the element composition ratio on the surface using EDX. A large amount of fluororesin derived from the binder was observed in positive electrode D, which means that when the solvent dries rapidly from the current collector foil side to the electrode surface side under high temperature conditions as shown in the figure, the fluororesin dissolved in the solvent becomes unevenly distributed and precipitates on the electrode surface. This phenomenon is called binder migration.

[0064] Methods for identifying the material nonuniformity in the electrode composite sheet caused by this binder migration include the SEM-EDX analysis of the sheet surface shown in Figure 7, as well as cross-sectional observation of the sheet and contrast analysis using surface SEM.

[0065] Figure 12 shows the results of cross-sectional SEM observation of one embodiment of the inspection system of the present invention. The sheets in the figure are the same electrodes B and D as in Figure 11. In this measurement, in order to quickly determine the quality of the sheet during the manufacturing process, sample pieces were extracted by punching using a processing jig including a metal or ceramic blade, and the cross section was not polished before observation.

[0066] Figure 12 (a) is a secondary electron image, and (b) is a mapping of the abundance ratio of fluorine (F) derived from the binder measured by EDX. It can be seen that in positive electrode D, which was dried at high temperature and in which binder migration has progressed, the fluorine element is distributed unevenly and is concentrated in the surface layer of the sheet. This information can also be accumulated as structural information.

[0067] FIG. 13 shows a schematic diagram of a method for quantifying and extracting structural information from a surface SEM observation image, which is one embodiment of the inspection system of the present invention. (i) is an observation image (backscattered electron image, BSE image) obtained by detecting backscattered electrons (BSE) from an observation object in response to irradiated electrons in an SEM. In a secondary electron image, the brightness increases as the atomic weight of the observation object increases, and in FIG. 13, the contrast of the active material (NCM) region is dark, and the surrounding binder and conductive additive regions are observed as faint. In addition, void regions where nothing exists are observed as black. Taking advantage of this, in FIG. 13, after removing noise in the image in (ii), the active material region, binder and conductive additive region, and void region are identified by the brightness of the contrast in (iii), and the composition of the constituent materials on the sheet surface is quantified by their area ratio.

[0068] Figure 14 shows the results of quantifying the area ratios of the binder and conductive additive regions (intermediate color regions) in positive electrodes A to D using the method described above. In this measurement, evaluation results are shown for multiple observation regions on the surface of one sheet in order to correct measurement variability due to measurement location. The height of the bars in Figure 14 indicates the average value, and the variability is evaluated using error bars. The average area ratio of the intermediate color regions is higher for electrodes with higher drying temperatures and with a tendency for binder to be unevenly distributed on the surface, so the results in Figure 14 can be seen as a quantification of the uneven distribution of binder as structural information.

[0069] As another measurement method, highly adhesive conductive tape was attached to the surfaces of positive electrodes A to D, and this was used to peel off positive electrodes A to D from the current collecting foil, confirming electrode peeling in the area close to the current collecting foil. Therefore, SEM observation was similarly performed on the peeled surface on the current collecting foil side, and the ratio of intermediate color areas to the peeled surface was calculated using the same method as in Figure 13. It was confirmed that positive electrode D, which had a high drying temperature, had the least intermediate color areas, confirming that this method can also detect binder uneven distribution on the electrode surface due to drying at high temperatures.

[0070] Figure 15 shows the discharge rate characteristics, which is one of the battery performance characteristics measured before shipment. The horizontal axis is the discharge rate, and xC means the amount of current that can charge or discharge the amount of electricity that can be stored in the battery in 1 / x time. In Figure 15, it is thought that the higher the rate (higher the current value), the lower the discharge capacity due to the influence of the resistance inside the battery, and this tendency was prominent in positive electrode A, which was dried at a low temperature, and positive electrode D, which was dried at a high temperature. Here, in order to quantitatively evaluate the influence of the change in electrode structure depending on the manufacturing conditions on the ion conduction resistance in the electrode, symmetric cells were prepared by sandwiching a separator between the same two positive electrode sheets for positive electrode A to positive electrode D, and electrochemical impedance (EIS) measurements were performed at 25°C.

[0071] The results are shown in Figure 16. The length of the region close to the 45° angle in the plot in the figure corresponds to the magnitude of the ionic conduction resistance, and the ionic conduction resistance of each positive electrode was evaluated from this. The results are shown in Table 1. This suggests that when the binder is unevenly distributed on the surface, as in positive electrode D, the binder on the outermost surface of the electrode inhibits the movement of electrons and ions to the active material, increasing the resistance.

[0072] In addition, in positive electrode A, where the drying temperature was low and the amount of binder on the surface was small, it is expected that the binder is relatively unevenly distributed near the current collecting foil, and as a result, it can be considered that the ion conduction resistance increased. Table 1 shows the ratio of the discharge capacity at 0.2 C (coulomb) to the discharge capacity at 5 C as an example of performance information, and the order is Positive Electrode B~Positive Electrode C>Positive Electrode A>Positive Electrode D, which is consistent with the ranking of ion conduction resistance (from lowest to highest: Positive Electrode B~Positive Electrode C<Positive Electrode A<Positive Electrode D).

[0073] Figure 17 shows the results of a charge-discharge cycle test simulating the deterioration of battery performance during operation. Positive electrodes A to D were combined with negative electrodes of the same specifications made of graphite to produce laminated battery cells, and a charge-discharge cycle test was performed at a rate of 1C (coulomb) in a constant temperature environment of 25°C.

[0074] The rate of capacity decline in the battery cells using positive electrodes A and D was larger than that in the cells using positive electrodes B and C, and was particularly notable in the case of positive electrode D. In addition, the battery internal state parameters shown in Figure 9 were obtained by comparing the voltage-capacity curve and the resistance-capacity curve before and after degradation, and the active material utilization rate m p The change in capacity decline rate differed for each positive electrode, being: positive electrode A (93.1%), positive electrode B (99.5%), positive electrode C (99.0%), and positive electrode D (76.5%). This order was consistent with the order of the capacity decline rate.

[0075] In addition, a battery disassembly test after the test revealed that in positive electrode D, where the active material utilization rate was significantly reduced, defects occurred between the electrode composite sheet and the Al current collector foil, and the uneven distribution of the binder on the surface layer confirmed in Figures 11 to 14 deteriorated the bonding between the electrode composite and the current collector foil, impairing the utilization of the positive electrode portion at the non-bonded portion, resulting in a significant reduction in the active material utilization rate of the positive electrode. Table 1 shows the discharge capacity retention rate after 150 cycles in the cycle test as an example of deterioration information, and it was found that the order was positive electrode B to positive electrode C > positive electrode A > positive electrode D, as in Figures 15 and 16.

[0076] FIG. 18 shows the performance information (ion conduction resistance in the electrode, 5C capacity / 0.2C capacity in the discharge rate test) and deterioration information (capacity retention rate after 150 cycles, deterioration rate of the positive electrode active material utilization rate (positive electrode active material utilization rate normalized per cycle m p The figure plots the area ratio of intermediate color regions, which is one piece of structural information, against the area ratio of intermediate color regions (rate of decrease in area). The figure also shows the results of regression analysis (here, fitting with a quadratic function) when performance information or degradation information is used as the objective variable and structural information is used as the explanatory variable. This study revealed that the area ratio of intermediate color regions is extremely sensitive to any of the performance information or degradation information.

[0077] This means that the initial performance and degradation characteristics of the battery to be manufactured later are determined by the binder ratio present on the surface obtained from the observation image of the positive electrode surface, and it was shown that it is possible to determine the electrode mixture layer that can guarantee the battery performance by inspecting and managing this structural information during manufacturing. Specifically, a part of the continuously manufactured electrode mixture sheet is extracted by the method shown in Figure 6, and the processes from fixing to the inspection holder, transport to the SEM device, atmosphere adjustment, backscattered electron image acquisition, and evaluation of the area ratio of the intermediate color region are automatically performed under pre-set conditions, and the obtained area ratio is input into the performance prediction model and degradation prediction model that have been constructed in advance, and it is possible to predict the initial performance and degradation performance during operation when a battery cell is manufactured using a wound body made of the corresponding electrode mixture sheet.

[0078] If the prediction result falls below a desired standard (predetermined performance), the electrode can be determined to be at risk of being defective. If the electrode is determined to be at risk of being defective, a notification to that effect can be given. The notification is preferably displayed on the monitor screen of a computer in the quality control system. A system operator can see the display on the monitor and remove batteries at risk of being defective from the line in advance. Alternatively, there may be a mechanism that automatically removes batteries determined to be at risk of being defective from the line.

[0079] Furthermore, by formulating the correlation as shown in the graph in Figure 18, it is possible to predict performance or degradation parameters from structural parameters that are quantified structural information, which is also useful for efficiently determining manufacturing conditions at the start-up of the battery manufacturing process. In addition, in this study, for simplicity, we focused only on the area ratio of the intermediate color region as structural information, but the porosity and the size of aggregates made of multiple active materials also change depending on the drying temperature, and by performing multiple regression analysis with these, the prediction accuracy of performance and degradation characteristics for quality control is improved.

[0080] The present invention is not limited to the above-mentioned embodiment, and various modified examples are included. For example, the above-mentioned embodiment shows an example of a positive electrode in which the drying temperature in the manufacturing information is changed over a wide range and the drying speed is significantly different in order to explain the present invention in an easy-to-understand manner. However, in an actual manufacturing line, the drying temperature set by the device is often constant, but the drying condition changes depending on the lot of the active material, the solvent mixing ratio, the slurry viscosity, the manufacturing line environment, etc., and the material distribution in the electrode changes. Even in such a case, it is possible to detect defects in the electrode mixture sheet that cause poor performance by the inspection method and procedure according to the first embodiment.

[0081] Also, while Figure 18 plots the correlation between structural information, performance information, and degradation information for four positive electrode composite sheets as a simple example, in reality, correlations are found from information groups for many electrodes, and formulated to be used for automatic pass / fail judgment. At this time, it is also possible to determine the coefficients of a preset model formula, or to analyze information groups for many electrodes using machine learning to derive the correlation formula.

[0082] Regarding the structural information, in addition to the distribution of the constituent materials in Example 1, the aggregate size of the active material particles, the shape of the voids formed between the materials, and the area ratio on the electrode surface can also be applied as structural information. In addition to the electrode surface, the distribution in the thickness direction and the curvature of the voids can be inspected and quantitatively evaluated using a scanning electron microscope or an optical microscope, and can be applied to structural information. As a method for confirming the distribution in the thickness direction, in addition to observation and analysis from the cross-sectional direction as shown in FIG. 12, observation and analysis from the surface direction of the electrode mixture sheet as shown in FIG. 13, the electrode mixture sheet can be peeled off from the current collector foil, and the peeled surface can be observed and analyzed, and the two can be compared to evaluate the uniformity in the thickness direction. [Explanation of symbols]

[0083] 100 cell (battery cell, secondary battery cell, secondary battery, lithium ion battery), 1 electrode occupying portion, 2 positive electrode terminal (tab), 3 negative electrode terminal (tab), 4 electrolyte, 5 separator, 6 exterior material, 11 positive electrode, 12 negative electrode, 111 positive electrode electrode composite layer, 112 positive electrode current collector foil, 121 negative electrode electrode composite layer, 122 negative electrode current collector foil, 311 current collector foil, 312 active material A, 313 conductive assistant, 314 binder, 315 active material B.

Claims

1. Information relating to the manufacture of an electrode mixture sheet to be applied to a positive electrode and / or a negative electrode of a secondary battery, the manufacturing information including at least one of a material specification, a manufacturing lot of a material, a mixing condition, a coating condition, and a pressing condition for forming the electrode mixture sheet; information related to the structure of the electrode mixture sheet measured after production, the information including at least one of the following: the presence or absence of defects or cracks in the positive electrode and / or negative electrode, the ratio of constituent materials in the in-plane or thickness direction of the electrode mixture sheet, the size of aggregates made of the constituent materials, cracks occurring inside electrode active material particles, and a void ratio where no constituent materials are present; Information on the performance of a secondary battery manufactured using the electrode mixture sheet, the information including at least one of a capacity at the time of initial charge / discharge, a charge / discharge efficiency which is a ratio of a capacity at the time of charge / discharge, a battery capacity when a charge or discharge current is changed, an AC resistance and a DC resistance at a predetermined charge rate; A quality control system for secondary batteries comprising a storage device that stores the manufacturing information, the structure information, and the performance information in association with each other.

2. 2. The quality control system for secondary batteries according to claim 1, A quality control system for secondary batteries, characterized in that the structural information is obtained by analysis using at least one of elemental analysis of a sample using a scanning electron microscope, an optical microscope, a blackness measurement method, or X-ray spectroscopy attached to the scanning electron microscope.

3. 3. The quality control system for secondary batteries according to claim 2, A quality control system for secondary batteries, characterized in that the structural information is information obtained by extracting a portion of the electrode composite sheet after manufacture by punching or processing using a laser, fixing it to an inspection holder, and analyzing it using at least one of the scanning electron microscope, the optical microscope, the blackness measurement method, or X-ray spectroscopy attached to the scanning electron microscope.

4. 4. The quality control system for secondary batteries according to claim 3, The structural information includes, for a part of the electrode mixture sheet fixed to the inspection holder, the number of defects between active materials per unit area, information on the area ratio, and the total number of cracks or crack lengths in the active material per unit area, based on a secondary electron image of the scanning electron microscope; Based on the backscattered electron image of the scanning electron microscope, the size of the regions with different contrasts reflecting the atomic weights of the constituent elements, the aggregate size obtained by quantifying the area ratio, the ratio of the constituent materials in the in-plane or thickness direction, and the void ratio, A quality control system for secondary batteries, comprising at least one of the above.

5. 2. The quality control system for secondary batteries according to claim 1, The association of the manufacturing information, the structure information, and the performance information in the storage device is A quality control system for secondary batteries, characterized in that the manufacturing conditions are controlled to produce electrode mixture sheets having different structures, and the relationship between the structural information obtained from the electrode mixture sheets and the performance information of batteries produced from the electrode mixture sheets is formulated by regression analysis.

6. 6. The quality control system for secondary batteries according to claim 5, Until the correlation coefficient of the correlation function obtained by the regression analysis becomes equal to or less than a predetermined value, A quality control system for secondary batteries, characterized in that a regression analysis of the relationship between the structural information obtained from the electrode mixture sheet in which only specific manufacturing conditions are changed and the performance information of a battery produced from the electrode mixture sheet is repeated to construct a performance prediction model.

7. In the quality control system for secondary batteries according to any one of claims 1 to 6, The information to be stored in the storage device in association with the manufacturing information, the structure information, and the performance information further includes information showing a change in battery performance due to use of the battery incorporated into the storage battery system after shipment, the deterioration information including at least one of a capacity maintenance rate, a resistance increase rate, a rate of decrease in the utilization rate of the active materials of the positive electrode and the negative electrode, and a rate of increase in the ion conduction resistance in the battery; A quality control system for a secondary battery comprising:

8. 8. The quality control system for secondary batteries according to claim 7, The association of the manufacturing information, the structure information, the performance information, and the degradation information in the storage device is A quality control system for secondary batteries, characterized in that the manufacturing conditions are controlled to produce electrode mixture sheets having different structures, and the relationship between the structural information obtained from the electrode mixture sheets and the deterioration information of batteries produced from the electrode mixture sheets is formulated by regression analysis.

9. 9. The quality control system for secondary batteries according to claim 8, Until the correlation coefficient of the correlation function obtained by the regression analysis becomes equal to or less than a predetermined value, A quality control system for secondary batteries, characterized by repeating regression analysis of the relationship between the structural information obtained from the electrode mixture sheet in which only specific manufacturing conditions are changed and the deterioration information of the battery produced from the electrode mixture sheet, and constructing a deterioration prediction model.

10. The quality control system for the secondary battery according to any one of claims 1 to 6, 2. A quality control system for secondary batteries, wherein the secondary battery is any one of a lithium ion secondary battery, a sodium ion secondary battery, a potassium ion secondary battery, and a secondary battery using a polyvalent cation as a carrier.

11. In the quality control system for secondary batteries according to any one of claims 1 to 6, The quality control system for secondary batteries, wherein the electrode mixture sheet used in the secondary batteries contains a solid electrolyte.

12. In the quality control system for secondary batteries according to any one of claims 1 to 6, A quality control system for secondary batteries, characterized in that the electrode mixture sheet is formed by forming a slurry of a mixture of constituent materials together with a liquid, coating and drying the slurry, and then applying pressure.

13. In the quality control system for secondary batteries according to any one of claims 1 to 6, A quality control system for secondary batteries, characterized in that the electrode mixture sheet is formed by dispersing a mixture of constituent materials in a solid state into a sheet and applying pressure.

14. A method for quality control of a secondary battery, comprising using the quality control system for a secondary battery according to any one of claims 1 to 6.

15. A quality control method for a secondary battery using the quality control system for a secondary battery according to any one of claims 1 to 6, comprising the steps of: extracting the performance information for a particular battery from the performance information stored in the storage device in association with the structural information extracted after manufacture of the battery; A quality control method for a secondary battery, comprising the steps of: notifying the user when performance information of the battery does not satisfy predetermined performance information.

Citation Information

Patent Citations

  • Automatic check method for appearance defect of continuous porous electrode base material and winding body of porous electrode base material with its recording medium

    JP2010272250A

  • Method for detecting defective product

    JP2015133259A

  • Method for inspecting electrode for power storage device

    JP2016143641A